Pemberdayaan kader posyandu lansia untuk meningkatkan kemandirian keluarga dalam perawatan pasca stroke - Upoyo, Arif Setyo; Sri Rejeki, Dwi Sarwani; Sutrisna, Eman (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2025)
Introduction: The problems that post-stroke patients still face after being hospitalized are weakness in one side of the body (hemiparesis), speech disorders (dysarthria/aphasia), difficulty swallowing (dysphagia) and psychological disorders such as post-stroke depression and the risk of recurrent attacks. The purpose of the service is to improve the knowledge and skills of partners about: early detection of stroke, post-stroke care, post-stroke physical exercise, post-stroke speech therapy, post-stroke swallowing therapy, post-stroke psychological management. The method carried out is training with lectures, discussions and demonstrations, the media used are modules and videos. The participants were elderly Posyandu cadres and families who took care of family members after a stroke totaling 19 people. The success of the training was evaluated by comparing pre and posttest scores and assessing the participants' ability to demonstrate the actions taught. The results obtained by the knowledge of early detection, psychological management and post-stroke care of participants were 100% improved. Skills about early detection of stroke, ROM exercises, swallowing exercises and speech therapy 89.47% of participants improved. Conclusion: The training is effective in improving the knowledge and skills of cadres and families in caring for post-stroke patients. Key word: post-stroke, training, cadres, family, care